Eumasia venefica sp. nov. a new species of the subfamily Eumasiinae (Lepidoptera: Psychidae) from India with atypical larval ecology - Unnikrishnan, Usha Ayyath; Sobczyk, Thomas; Jose, Roby Thekkudan; Jose, Joyce (Zootaxa, 2023)
A new species of bagworm moth, Eumasia venefica sp. nov., from the subfamily Eumasiinae, is described from Kerala, India. This species has a peculiar larval ecology, larval case structure and an association with lichens. The paper describes the detailed taxonomy of the adult and the larval stages of the species.